Persistent Dyslipidemia in Austrian patients treated with statins for primary and secondary prevention of atherosclerotic events - Results of the dyslipidemia international study (DYSIS) = Persistente Dyslipidämie in Österreich bei Patienten, die zur Primär- und Sekundärprävention atherosklerotischer Ereignisse mit Statinen behandelt waren – Ergebnisse der Dyslipidemia International Study (DYSIS) - Drexel, Heinz; Chazelle, Francois; Fauer, Christiane; Lautsch, Dominik; Gitt, Anselm Kai (Wiener klinische Wochenschrift, 2011)
BACKGROUND: Statins reduce cardiovascular events by about one third; thus two out of three events occurring without any lipid lowering treatment still might happen under statin treatment. One reason may be that lipid targets are not met. The DYSlipidemia International Study (DYSIS) was performed to determine the prevalence of persistent dyslipidemia despite statin treatment in Austria. PATIENTS AND METHODS: Between April 2008 and February 2009, 910 outpatients on current statin treatment and aged ≥ 45 years were recruited by general practitioners, cardiologists, endocrinologists, and internists. A clinical examination was performed and lipid values were obtained under stable statin therapy. The ESC guidelines version 2007 served as criteria to judge the attainment of treatment targets for LDL cholesterol and to reach normal HDL cholesterol and triglyceride levels. In 765 patients a full lipid profile including fasting cholesterol, fasting triglycerides, HDL-cholesterol, and LDL-cholesterol could be obtained. RESULTS: Of our patients, 74.5% had at least one lipid parameter not at target. Specifically, 52.3% did not reach the LDL-cholesterol target as according to the ESC guidelines 2007 - and 56.4% as according to the Austrian lipid consensus 2010 -, 59.1% had above-target total cholesterol levels and 42.5% had elevated triglyceride levels. In 23% of the patients the HDL cholesterol was below levels associated with increased cardiovascular risk. In patients with only one single value beyond normal or targeted level, LDL cholesterol had a prevalence of 24.3%, HDL of 11.9% and triglycerides of 24.5%. In 8.4% of patients, all 3 parameters, LDL-cholesterol, HDL-cholesterol and triglycerides, were out of range. CONCLUSIONS: About three quarters of the Austrian patients under chronic statin therapy in routine clinical practice failed to meet lipid values as set by international and Austrian guidelines. There is an urgent need for more effective strategies to better control dyslipidemia in statin treated patients with the aim of further reducing cardiovascular events.